2022
DOI: 10.1017/s0022215122000494
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of artefact reduction possibilities with the new active transcutaneous bone conduction implant (Bonebridge)

Abstract: Objective This study aimed to evaluate the possibilities of artefact reduction using different anatomical implant positions with the Bonebridge bone-conduction hearing implant 602 for a patient with an acoustic neuroma requiring regular diagnostic magnetic resonance imaging of the tumour position. Method Three implant positions and magnetic resonance imaging examinations with and without customised sequences for metal artefact suppression were investigated. The diagnostic usefulness was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Even though the size of the BC-FMT in the new generation, the BCI602, was reduced, requiring a drilling depth compareable to that of a BAHA-screw, still in patients with comorbid intracranial tumour or cholesteatoma necessitating regular imaging control with MRI the artefact may is a disadvantage compared to percutaneous implants. Recent studies by Edlinger et al and Utrilla et al adressed this possible problem by investigating artefact reduction possibilities with the BCI602 and concluded, that with the application of artefact reduction sequences and certain anatomical placements also tumour- and cholesteatoma cases can be diagnosed succesfully [ 11 , 12 ]. Especially, the reduced depth of the implant makes pre-surgical planning redundant and with the new MRI possibilities open new possibilities for difficult anatomies as well as the option to implant children younger than 5 years of age [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the size of the BC-FMT in the new generation, the BCI602, was reduced, requiring a drilling depth compareable to that of a BAHA-screw, still in patients with comorbid intracranial tumour or cholesteatoma necessitating regular imaging control with MRI the artefact may is a disadvantage compared to percutaneous implants. Recent studies by Edlinger et al and Utrilla et al adressed this possible problem by investigating artefact reduction possibilities with the BCI602 and concluded, that with the application of artefact reduction sequences and certain anatomical placements also tumour- and cholesteatoma cases can be diagnosed succesfully [ 11 , 12 ]. Especially, the reduced depth of the implant makes pre-surgical planning redundant and with the new MRI possibilities open new possibilities for difficult anatomies as well as the option to implant children younger than 5 years of age [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, artifacts are an issue only if the examination area is very close to the HI, namely in the skull region. Several studies showed that the application of artifact reduction sequencing and an adaptive positioning of the implant enable regular MRI examinations of the region without affecting the diagnostic image quality for diagnostics [ 30 , 31 , 32 ]. Our survey established that all the MRI scans performed with MED-EL HIs occurred without any magnet dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…Complications concerning MEI described in the literature occurred solely when the magnet strength of the MRI scanners was higher than that recommended by the manufacturer (1.5 T for MEI) [ 11 ]. The only complication described with BCI is the occurrence of artifacts which may be successfully improved by artifact reduction sequencing [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Furthermore, 2 articles reported on the artifact reduction possibilities in magnetic resonance imaging by the new system BB602. 11,12 The aforementioned smaller dimension of BB602 simplifies the implant placement, even in demanding anatomical considerations. Furthermore, it facilitates implantation without the use of implant lifts.…”
mentioning
confidence: 99%
“…Besides noted studies, several case reports and case series could be identified, also reporting on satisfactory results after BB602 surgery 8‐10 . Furthermore, 2 articles reported on the artifact reduction possibilities in magnetic resonance imaging by the new system BB602 11,12 …”
mentioning
confidence: 99%